OC-077 The international cooperative study evaluating the effect of fully covered self-expanding metallic stents compared with plastic stents for resolution of pancreatic ductal strictures and pain relief in patients with chronic pancreatitis. (17th June 2017) - Phillips, N; Siddiqui, A; Wadsworth, C; Vlavianos, P; Diehl, D; Kowalski, T; Loren, D; Sharaiha, R; Westaby, D
Abstract : Introduction: Endoscopic placement of plastic stents (PS) is first-line therapy for pancreatic duct strictures in patients with chronic pancreatitis. Fully covered, self-expandable metal stents (cSEMS) offers an alternative to plastic stents for stricture resolution. Method: Patients at 6 tertiary centres with a dominant stricture in the pancreatic head and abdominal pain who underwent an ERCP were divided into 2 groups: 1) those that underwent PS placement and 2) those that underwent cSEMS placement. Technical success (successful stent placement), stricture resolution rate, pain reduction, and AEs were evaluated in both groups. Results: A total of 185 patients between 2011 and 2016 were included: 93 underwent cSEMS placement and 92 had PS placed. The etiologies of chronic pancreatitis were predominantly due to alcohol (55%). All patients in the cSEMS and 77% in the PS groups had daily opioid use for pain control. 57% patients in the cSEMS group had failed previous endotherapy with PS. There were no significant differences in cSEMS and PS groups with regards to technical success (99% vs. 100%) or overall procedural AEs (8.6% vs. 5.4%; p=0.4). Post-ERCP pancreatitis was 4% with cSEMS and 3.2% with PS (p=1). Stricture resolution was achieved in 86% patients with cSEMS and in 55.4% patients with PS (OR 4.95; p<0.001). The median number of ERCPs to obtain stricture resolution was lower with cSEMS: 1.5 vs. 3.9 (p=0.002). Of those who achieved stricture resolution, 27% patients in the cSEMS group and 40% in the plastic stent group developed symptomatic stricture recurrence (p=0.06). A significantly lower number of patients in the cSEMS group were referred for surgical therapy as compared to the PS group (14% vs. 28%; p=0.02). A higher number of patients in the cSEMS group were able to decrease their opioid dosage as compared to the PS group (62% vs. 51%; p=0.14). On multivariate analysis, use of cSEMS was an independent predictor of pancreatic stricture resolution (OR 2.58; p=0.05). Conclusion: cSEMS are associated with improved resolution of dominant pancreatic duct strictures in the pancreatic head/neck with fewer endoscopic sessions when compared with plastic stents. A greater number of patients with cSEMS were able to decrease their opioid dosage as compared to the PS group. Disclosure of Interest: None Declared